2006
DOI: 10.1007/s10286-006-0307-x
|View full text |Cite
|
Sign up to set email alerts
|

Subtle involvement of the parasympathetic nervous system in patients with irritable bowel syndrome

Abstract: This study comprises assessment of autonomic function in irritable bowel syndrome (IBS) patients, focusing on meal-related changes. In 18 IBS patients (4 males, mean age 45+/-3.0 [SEM] years) and 19 healthy volunteers (6 males, mean age 41+/-3.5 years) blood pressure, heart rate, heart rate variability and muscle sympathetic nerve activity (MSNA) were assessed before, during and after consumption of a standardized meal. In pre- and postprandial phase Valsalva maneuver, cold pressor test (CPT) and deep breathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…However, conflicting results exist as to how this imbalance is expressed. Some studies indicate changed sympathetic activity [10][11][12], and/or parasympathetic activity [8,9,[13][14][15][16][17][18], or specific autonomic functional abnormalities only in particular symptom subgroups [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, conflicting results exist as to how this imbalance is expressed. Some studies indicate changed sympathetic activity [10][11][12], and/or parasympathetic activity [8,9,[13][14][15][16][17][18], or specific autonomic functional abnormalities only in particular symptom subgroups [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus activation of nAChRs in DMV-projecting, GABAergic NTS neurons might effectively increase the gain of vagal circuits involved in reflexive inhibition of vagal motor output to the gut (Ferreira et al 2000). Effects of excess, exogenous nicotine might also alter normal brain-gut interactions, impairing autonomic homeostasis and ultimately contributing to symptoms of nicotine toxicity: emesis, dysphagia, gastric stasis, and irritable bowel syndrome (Aggarwal et al 1994;Camilleri 1990;Camilleri and Bharucha 1996;van Orshoven et al 2006). In humans, smoking cessation leads to significant gains in body weight, affecting the efficacy of smoking cessation programs (Nordstrom et al 1999;Pomerleau et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that IBS can be accompanied to the autonomic nervous system dysfunction in various publications [12][13][14][15][16]. These conditions may cause changes in the electrical activity and contraction problems of the heart.…”
Section: Discussionmentioning
confidence: 99%